2008
DOI: 10.2174/156800908783769346
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor: Renaissance as a Cancer Therapeutic?

Abstract: Since the discovery of tumor necrosis factor (TNF)-alpha, researchers have pursued many approaches to harness the potency of TNF-alpha and TNF superfamily members to treat human cancers. Several ligands of the TNF superfamily, including TNF-alpha, lymphotoxin, FAS ligand (FasL), and APO2 ligand/TNF-related apoptosis-inducing ligand (Apo2L/TRAIL) have been tested in various stages of clinical research for their anti-tumor efficacy. Moreover, several antibodies to TNF receptor (TNFR) superfamily members are now … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 144 publications
(177 reference statements)
1
41
0
3
Order By: Relevance
“…Production of TNF-α by OSCC cells could result in resistance to the cytotoxic action of host derived TNF-α or exogenous recombinant TNF-α administered in a therapeutic setting. TNF-α has been used in several clinical trials in cancer patients and has resulted in no significant improvements in survival (Sherman et al, 1988;Daniel et al, 2008). Local production by tumor cells and their consequent resistance may in part explain these disappointing results.…”
Section: Discussionmentioning
confidence: 99%
“…Production of TNF-α by OSCC cells could result in resistance to the cytotoxic action of host derived TNF-α or exogenous recombinant TNF-α administered in a therapeutic setting. TNF-α has been used in several clinical trials in cancer patients and has resulted in no significant improvements in survival (Sherman et al, 1988;Daniel et al, 2008). Local production by tumor cells and their consequent resistance may in part explain these disappointing results.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a has demonstrated potent antitumor activity in animal models. 36 Despite some observed toxicity in preclinical models, its potent activity against human tumor xenografts led to clinical trials in humans. However, the results were a small number of minimal responses with extensive hemodynamic side effects and hepatic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results were a small number of minimal responses with extensive hemodynamic side effects and hepatic toxicity. 36 Those trial results were sufficiently disappointing that studies of systemically delivered, single-agent TNF-a were discontinued. To avoid systemic toxicity, currently, TNF-a is used clinically only in isolated organ perfusion for human melanoma and soft tissue sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors are characterized by a death domain in the cytoplasmic tail which transduces signals from their cognate ligands such as TNFα, Fas ligand (FasL) and TNF-related apoptosis inducing ligand (TRAIL). Despite disappointing results from early clinical trials for recombinant TNFα, which showed severe toxicity after systemic exposure (5,6), there is a continued effort to separate the unwanted toxicities from its potent apoptosis inducing activity by modifying TNF protein; for example, NGR-TNFα fusion protein (7) and TNFα-colloidal gold nanoparticles (8) are currently in clinical trails for treating human cancers.…”
Section: Introductionmentioning
confidence: 99%